We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
225
2
avatar

How to get from this:

sk1/3 = δk.

 

to this

 

k2/3 = s

k = (s/δ)3/2.

 Apr 16, 2018
 #1
avatar+21991 
0

How to get from this:

sk1/3 = δk.

 

to this

 

k2/3 = s/δ

k = (s/δ)3/2.

 

\(\begin{array}{|rcll|} \hline \delta k \quad &=& sk^{\frac{1}{3}} \quad & | \quad : \delta \\\\ k &=& \dfrac{s}{\delta} k^{\frac{1}{3}} \quad & | \quad k = k^1 \\\\ k^1 &=& \dfrac{s}{\delta} k^{\frac{1}{3}} \quad & | \quad k^1=k^{\frac{3}{3}} \\\\ k^{\frac{3}{3}} &=& \dfrac{s}{\delta} k^{\frac{1}{3}} \quad & | \quad : k^{\frac{1}{3}} \\\\ \dfrac{ k^{\frac{3}{3}} } { k^{\frac{1}{3}} } &=& \dfrac{s}{\delta} \\\\ k^{\frac{3}{3}} k^{-\frac{1}{3}} &=& \dfrac{s}{\delta} \\\\ k^{\frac{3}{3}-\frac{1}{3}} &=& \dfrac{s}{\delta} \\\\ k^{\frac{3-1}{3}} &=& \dfrac{s}{\delta} \\\\ k^{\frac{2}{3}} &=& \dfrac{s}{\delta} \\\\ \left(k^{\frac{2}{3}}\right)^{\frac{3}{2}} &=& \left(\dfrac{s}{\delta} \right)^{\frac{3}{2}} \\\\ k^{\frac{2}{3}\cdot \frac{3}{2}} &=& \left(\dfrac{s}{\delta} \right)^{\frac{3}{2}} \\\\ k^{1} &=& \left(\dfrac{s}{\delta} \right)^{\frac{3}{2}} \\\\ k &=& \left(\dfrac{s}{\delta} \right)^{\frac{3}{2}} \\ \hline \end{array}\)

 

 

laugh

 Apr 16, 2018
 #2
avatar
0

Thank you very mutch :D

Guest Apr 16, 2018

15 Online Users